Ketidakpercayaan terhadap Layanan Kesehatan: Kurangnya Kesediaan Ibu Hamil Menggunakan Layanan Rumah Tunggu Kelahiran di Kabupaten Wonogiri: Distrust of Healthcare Services: Pregnant Women’s Lack of Willingness to Use Maternity Waiting Home Service in Wonogiri Regency - Sri Hilmi Pujihartati; Mahendra Wijaya; Argyo Demartoto (Society, 2021)
To reduce the maternal mortality rate, a health service program that ensures the good health of pregnant women is needed. Maternity Waiting Home (MWH) is a program to reduce maternal mortality. This program is implemented in various regions in Indonesia, and the one is in Wonogiri Regency. In its implementation, it is not uncommon to find obstacles that come from various parties. This study uses a qualitative descriptive method to explain the Maternity Waiting Home (MWH) service and its distrust. This study seeks to explain the trust of various stakeholders, especially pregnant women, in the Maternity Waiting Home (MWH) service in Wonogiri Regency. Focus Group Discussions (FGD) and interviews were conducted to collect data by generating samples from various stakeholders. In reality, the Maternity Waiting Home (MWH) service in Wonogiri Regency experiences obstacles, especially from the trust of its users. Many pregnant women are unwilling to use the Maternity Waiting Home (MWH) service for several reasons. There is distrust in the service because of many factors. This study concludes that Maternity Waiting Home (MWH) service stakeholders in Wonogiri Regency should address and fix this important problem by intensifying socialization about the urgent of Maternity Waiting Home (MWH) service.